DSM in Thailand : A Case Study - Singh, Jas (World Bank, Washington, DC, 2014)
In 1993, Thailand initiated a demand-side management (DSM) program to help curb electricity demand growth and promote more energy-efficient equipment and cost-effective energy services within the country. Since then, the Electricity Generating Authority of Thailand (EGAT), the national generation and transmission utility's DSM Office has developed a strong portfolio of DSM measures, including 19 DSM programs targeting a wide range of sub-sectors and end-uses, and substantially surpassed its original peak reduction and energy conservation targets. EGAT has created substantial public awareness of energy conservation and actively promoted private sector participation in promoting such services. And, EGAT's DSM Office has been recognized internationally for its success in designing DSM programs that fit within an Asian context as well as its innovation and partnershis with other agencies. While the overall Program results have been positive, EGAT has had limited impacts in certain areas and experienced a number of implementation issues, many of which are now being resolved. This report examines the creation of Thailand's DSM program, discusses programs and results to date, offers analyses and lessons learned from the Program, and discusses future prospects for DSM programs in Thailand and elsewhere.